APPLICATION OF MAKE A MATCH COOPERATIVE LEARNING MODEL ASSOCIATED WITH MEDIA CARD TO INCREASE SCIENCE LEARNING OUTCOMES - Dwi Lestari Nur Fiddiniya; Izzatul Muslimah; Auliya Niswatul Farichah; Junia Saptaningrum (Citra Dharma Cindekia, 2022)
Teachers who use the lecture method too often often make learning boring. One of the subjects considered boring by students is Natural Sciences (IPA). In this study, the author uses the type of classroom action research (CAR). The purpose of this study was to determine the significant difference in learning outcomes between students who study with the cooperative learning model of make a match with the aid of card media and students who study conventionally. The results showed that all aspects of the application of the make a match cooperative learning model which were carried out in 2 cycles in science learning had been carried out and students experienced an increase in each cycle. The percentage of the classical value of the implementation of the first cycle of learning, which is 61.10%, is still categorized as incomplete. The percentage of the classical value of the implementation of the second cycle of learning is 88% which is included in the category of complete learning so that students can be said to be complete in participating in learning. Thus, it can be concluded that the application of the make a match type of cooperative learning model assisted by card media to improve science learning outcomes for fourth grade students at SDN Laladan has been successful.